2022
DOI: 10.3897/zse.98.72392
|View full text |Cite
|
Sign up to set email alerts
|

A new catfish of the genus Trichomycterus from the Rio Paraíba do Sul Basin, south-eastern Brazil, a supposedly migrating species (Siluriformes, Trichomycteridae)

Abstract: A new species of the catfish genus Trichomycterus is described from the Rio Paraíba do Sul, south-eastern Brazil. This species exhibits some morphological character states that are unique amongst congeners, including a robust opercle and a long interopercle with numerous odontodes (50–60 opercular and 90–100 interopercular), a black bar on the basal portion of the caudal fin and a dark brown flank with a well delimited dorsal yellow stripe. It also exhibits some morphological traits that are uncommon amongst c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Cambeva chrysornata is similar to C. cubataonis and is distinguished from C. guaratuba by the medial margin of the autopalatine exhibiting a deep concavity in its middle portion, posteriorly followed by a distinctive projection towards the mesethmoid. Cambeva chrysornata is also distinguished from C. cubataonis by having 14 vertebrae (vs. [15][16].…”
Section: Taxonomic Accountsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cambeva chrysornata is similar to C. cubataonis and is distinguished from C. guaratuba by the medial margin of the autopalatine exhibiting a deep concavity in its middle portion, posteriorly followed by a distinctive projection towards the mesethmoid. Cambeva chrysornata is also distinguished from C. cubataonis by having 14 vertebrae (vs. [15][16].…”
Section: Taxonomic Accountsmentioning
confidence: 99%
“…Cambeva guaratuba is also distinguished from C. chrysornata by having longer barbels, the tip of the rictal barbel posteriorly reaching area posterior to the orbit (vs. reaching the anterior margin of the orbit or an area anterior to it) and maxillary and rictal barbels reaching interopercular patch of odontodes (vs. not reaching), a relatively deep dorsal fin, with the longest ray longer than the dorsal-fin base (vs. longest ray shorter than the dorsal-fin base), pectoral fin subtriangular in dorsal view (vs. rounded), pelvic fin truncate, its posterior extremity reaching a vertical at the anterior half of the dorsal-fin base (vs. rounded, its posterior extremity reaching a vertical anterior to the dorsal-fin origin), more procurrent caudal-fin rays (total of 20 or 21 dorsally and 13 or 14 ventrally, vs. 16 or 17 dorsally and 11 or 12 ventrally), more vertebrae (40 or 41, vs. 38 or 39), and the absence of an irregularly shaped golden longitudinal line on the medio-dorsal portion of the flank (vs. presence). Cambeva guaratuba is also distinguished from C. cubataonis by having 14 vertebrae (vs. [15][16].…”
Section: Taxonomic Accountsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicated the existence of at least 21 trichomycterine species endemic to the Rio Paraíba do Sul basin ( [12,49,50] and included references), belonging to five different subgenera (i.e., Cryptocambeva, Humboldtglanis, Paracambeva, Psammocambeva, and Trichomycterus; [10]). Contrastingly, today, there are 16 nominal species of Trichomycterus considered endemic to RDB, of which 15 belong to Psammocambeva and only one, T. argos, belongs to Cryptocambeva.…”
Section: Comparing Species Diversity Of Trichomycterines In Rdb and I...mentioning
confidence: 99%